Chasing shadows - Harper, Karen (Karen S.) (Harper, Karen (Karen S.) South Shores., 2016)
Forensic psychologist Claire Britten and lawyer Nick Marwood team together to solve a murder in St. Augustine, Florida. An attraction between them blossoms, but once Claire discovers Nick's personal connections to the case, she may no longer be able to trust him.